Model Pengelolaan Penanggulangan Masalah Kurang Energi Protein Berbasis Pemberdayaan Masyarakat Di Desa Girirejo Kecamatan Imogiri Kabupaten Bantul - Abidillah Mursyid; Idi Setyobroto; Waryana Waryana (Jurnal Teknologi Kesehatan (Journal of Health Technology), 2016)
Protein energy malnutrition (PEM) is one of the nutritional problems in children in Indonesia. Results of basic medical research in 2013 showed that the prevalence of average malnutrition at national level was 6.65%, stunting was 18.5 %, and under-weight was 13.3 % (Riskesdas, 2010). In Yogyakarta Province the average 0.7 % prevalence of malnutrition, nutritional status is very short at 10.2 %, and the nutritional status of a very thin 2.6 % ( DIY Health Of?ce , 2010). Protein energy malnutrition problems in toddlers impact on the quality of Indonesia's young generation as the future generation, so it needs serious treatment. This study aims to create a long-term management model on nutrition improvement program. In particular, this study aims to analyze the role of local government in managing public nutrition improvement effort, to analyze community participation, and to develop management models of community-based nutrition program. This study was an observational study with qualitative approach. Design approach of this research was a case study. The study population was a group of villagers with activity to overcome protein energy malnutrition problem. The research sample of respondents was taken purposively. Sample size was determined by saturation. The data collected were the role of Girirejo local government, community participation, and the type of activity to overcome protein energy malnutrition problems. Data were analyzed interactively and simultaneously. The success of the program to overcome protein energy malnutrition problem in the Girirejo village was in?uenced by the local government's role in guiding community, and the role of government Sub District Imogiri, especially Imogiri I Health Centre. Internally the role of government in?uenced the increase of community participation and empowerment. The role of Girirejo local government was motivating, disseminating information, providing examples, raising awareness, guiding, mobilizing the community, facilitating and allocating resources. Meeting forum used to motivate Girirejo citizens was done through PKK (Family Wealth Education) meeting, household organisation, integrated service post, farmer groups, and yasinan (religious) meeting. The head of village and the head of public welfare department were the role model in guiding and managing program to overcome protein energy malnutrition problem.